Pregon mednarodnih hudodelstev in načelo zakonitosti - Zgaga, Sabina (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2017)
The majority of criminal prosecutions of core crimes' perpetrators in the last 60 years was performed post factum, since the rules of criminal prosecution were drafted after the commission of international crimes. The paper discusses the dilemmas, which arise from the principle of legality due to the post factum nature of criminal prosecution. First, the elements of principle of legality are presented, of which those are emphasised that could be controversial in case of international crimes prosecution. Afterwards, the paper discusses the answers provided by international criminal law, especially the case law of the International Criminal Tribunal for the former Yugoslavia and by the European Court of Human Rights. The paper concludes by analysis of Slovenian view on dillemas of principle of legality and compares Slovenian positions with the ones of the European Court of Human Rights. The thesis that Slovenian Constitution includes a stricter regulation of principle of legality than the European Court of Human Rights' system is thereby confirmed.
Keywords: criminal law; kazensko pravo; principle of legality; core crime; mednarodno pravo; načelo zakonitosti; statute of limitation; mednarodno hudodelstvo; definition of criminal act; lex mitior; zastaranje; opredelitev kaznivega dejanja; uporaba milejšega zakona